Admin Panel Sistem Verifikasi Permohonan Surat Keterangan Pengadilan Negeri Bale Bandung - Rizky Noviadi Ramadhan (Jurnal Penelitian Multidisiplin Ilmu, 2023)
The development of technology that continues to advance makes many companies begin to switch to digital use, many aspects in government agencies. Many online applications are a meeting place for public services and people who need them online. Bale Bandung District Court is a district court that has credibility in its field for public services. And what is happening now is that they want to have their own system to help develop online public services because they feel there are still gaps in the current system. Faced with the above problems, the author is allowed to help in designing a website that can be the foundation of what is expected for the development of an online application for verification of application letters using the waterfall method.This website was created using the PHP programming language because this language is very familiar when creating a website and is also easy to understand, almost all Indonesian people can easily access the website via computers, laptops and smartphones. We hope that the results of this website can assist the Bale Bandung District Court in improving the efficiency, accessibility and transparency of its public services, as well as providing convenience to the public to submit and verify petitions online. Thus, the court can be closer to the community and provide more modern solutions in the face of the ever-growing development of information technology.